Residue of biochar-organic fertilizer after one year of use on corn (Zea mays L.) plants in Alfisol - Widowati; Fikrinda, Wahyu; Wakhid; Umbu Kolambani , Frengky (AGROMIX, 2024)
Introduction: Nutrient-poor soil can lead to reduced crop yields. Biochar-organic fertilizer has demonstrated positive effects over several growing seasons. However, the efficacy of biochar-organic fertilizers varies based on the raw materials used and the duration of their application in the soil. This study aims to assess the residues of biochar, manure, and compost one year after their application on maize plants in Alfisol. Methods: A 300 kg/ha dosage was employed for a single treatment of biochar, manure, and compost. Additionally, biochar was combined with manure or compost at a dose of 150 kg/ha each. The experiment utilized a randomized block design with nine treatments and three replications, including a control group. The treatments comprised biochar made from coconut shell and husk, compost, manure, shell+compost biochar mixture, shell+manure biochar mixture, husk+compost biochar mixture, and husk+manure biochar mixture. Corn variety Pertiwi 3 was harvested upon reaching physiological maturity. Results: Combining husk biochar with chicken manure exhibited the most favorable response regarding plant height, leaf area, and weight. Furthermore, combining cob biochar and chicken manure yielded optimal cob length, weight without seeds, and seed weight. Conclusion: After one year, applying shell biochar mixed with manure demonstrated the most significant residual effect on corn plants.